Another one rides the bus - moving versus commuting decisions during the transition to higher education - Kubitza, Dennis [Verfasser]; Weßling, Katarina [Verfasser] (My University, 2025)
"The present study explores students’ decisions to either relocate or commute to their place of study depending on the availability of student tickets. By leveraging regional variations in the coverage of these subsidized public transport tickets, we explore whether their availability decreases students’ likelihood of moving. We investigate how the importance of subsidized tickets changes with commuting time and how their relevance varies based on students’ financial resources, social backgrounds, and risk attitudes. To do so, we use the MESARAS 2013 (Mobility, Expectations, Self-Assessment, and Risk Attitude of Students) survey, which queries university entrants in the field of economics at seven German universities. We link locational identifiers from the survey with the Google Distance Matrix API to assess commuting times and regional administrative data. Our logistic regression models suggest that the availability of student tickets may decrease the likelihood of moving. The association appears to be less pronounced as commuting time increases and seems to depend on parental academic status as well as students’ budget. Thus, our study offers three contributions: First, we provide policy-relevant evidence on the importance of affordable public transportation. Second, we address (social) inequalities in the moving versus commuting decision. Third, we demonstrate how accurate spatial modeling of commuting times and integration of survey data with external data sources benefits socio-spatial analysis." (author's abstract ; BIBB-Doku)

"Vorliegender Artikel untersucht Bedingungen, unter denen sich Studierende zwischen Umziehen und Pendeln zum Studienort entscheiden. Wir nutzen regionale Variationen in der Verfügbarkeit von Semestertickets, um zu analysieren, ob diese die Umzugswahrscheinlichkeit senken. Wir analysieren, ob und wie sich Semesterticketeffekte in Abhängigkeit von der Pendelzeit, den finanziellen Ressourcen, dem sozialen Hintergrund und der Risikoeinstellung der Studierenden verändern. Dazu verwenden wir die Daten der MESARAS 2013 (Mobility, Expectations, Self-Assessment, and Risk Attitude of Students) Erhebung, die Studienanfänger*innen in den Wirtschaftswissenschaften an sieben deutschen Universitäten befragt. Wir verknüpfen kleinräumige Standortinformationen aus der Erhebung mit Google Distance Matrix API zur Messung von Pendelzeiten, Daten zur Verfügbarkeit von Semestertickets von der Plattform waybackmachine.org und regionalen Verwaltungsdaten. Unsere logistischen Regressionsmodelle zeigen, dass die Verfügbarkeit von Semestertickets die Wahrscheinlichkeit des Umziehens senken kann. Dieser statistische Effekt scheint mit zunehmender Pendelzeit abzunehmen und außerdem vom akademischen Status der Eltern sowie vom verfügbaren Budget abzuhängen. Zusammenfassend leistet unsere Studie drei Beiträge: Erstens liefern wir politisch relevante Erkenntnisse zur Bedeutung des bezahlbaren öffentlichen Nahverkehrs. Zweitens gehen wir auf (soziale) Ungleichheiten bei Pendel- und Umzugs-Entscheidungen ein. Drittens demonstrieren wir, wie präzise räumliche Modellierungen von Mobilität durch die Integration von Umfragedaten mit externen Datenquellen sozialräumliche Analysen bereichern können." (Autorenreferat ; BIBB-Doku)
Keywords: G 1.3.3.3 Mobilität; S 1.4 Hochschulbildung; T 4.6 Wirtschafts- und Rechtswissenschaften; 370; 300; Mobilitätsbereitschaft; Studium; Wirtschaftswissenschaft; Regionale Mobilität; Pendler; Öffentlicher Personennahverkehr; Sozioökonomische Faktoren